Delphi: A social survey (2022) and some proposals for the sustainable development of the area - Kosmopoulos, Panos; Kantzioura, Athena; Fraggidou, Ioanna Pinelopi; Kleskas, Kostas (Technical Annals, 2023)
This project aims at the sustainable development of the area of Delphi under the scope of Environmental Design. Delphi is a historic place with multiple points of interest due to its natural beauty, archaeological importance and its traditional character. The project focuses upon the renovation and re-creation of a sustainable settlement, where all elements that concern the built environment and the urban area of Delphi, integrate morphologically as a whole. The proposal includes the traditional buildings’ restoration and the environmental and aesthetic upgrading of the buildings, the public open spaces and their partial elements. The project’s success depends on each place’s comparative advantage and on the promotion and protection of both the natural environment and the cultural heritage.